A three-dimensional numerical study of coupled photothermal and photoelectrical processes for plasmonic solar cells with nanoparticles. (March 2021) - Zhang, J.J.; Qu, Z.G.; Zhang, J.F.; Maharjan, A.
Abstract: Base on the GaAs plasmonic solar cell, a three-dimensional numerical model is proposed for the photoelectrical and photothermal processes. In the model, the coupled processes of nanoparticle photothermal conversion and substrate photoelectrical conversion are accounted for with FDTD solver and DEVICE solver. The Finite-Difference-Time-Domain method is used in the FDTD solver to analyze the light absorption process. The light absorption efficiency, quantum efficiency ratio of plasmonic solar cells to bare solar cells, and temperature distributions of the nanoparticles and substrate surface are obtained. A dimensionless coefficient for the substrate temperature rise is proposed to characterize the photothermal performance of the investigated plasmonic solar cell. The nanoparticles create parasitic absorption, increase substrate light scattering, and improve light absorption. Spherical Ag nanoparticles hold a higher photoelectrical conversion efficiency than spherical Au nanoparticles with an acceptable temperature increase, while spherical Au nanoparticles have stronger thermal sensitivity than spherical Ag nanoparticles. The cylindrical nanoparticles (Au or Ag) contribute significantly to the photothermal performance but do not contribute to the enhancement of the overall integrated quantum efficiency ratio. The nanoparticle arrays have accumulated heating and interference effects that enhance the thermal response. Spherical Ag nanoparticles are recommended for photoelectrical devices, while cylindrical Ag and Au nanoparticles are suitable for the development of thermal sensors. Graphical abstract: Image 1 Highlights: A 3D numerical model is proposed for performance of plasmonic solar cells with nanoparticles. Coupled nanoparticle photothermal and substrate photoelectrical conversion are accounted. Light absorption efficiency, quantum efficiency ratio and temperature distributions are obtained. Spherical Ag nanoparticles are recommended for photoelectrical devices. Cylindrical Ag and Au nanoparticles are recommended for thermal sensors.